Theatrical Geographies Alongside the History and the River (III): Seine River – via Marly – to Versailles - Stamatoiu, Cristian (Theatrical Research, 2022)
The study follows the cultural route fertilized by the Seine, after exiting Paris towards the west. It is about the impressive hydrographic adduction of the river with the help of the „Marly machine“, in order to animate the water games and the fireworks in the gardens of Versailles / Trianon palace during the reign of Louis XIV. In this space, a culture of the outdoors spectacle was developed, through royal entertainment and gallant games, but also via private theatrical performances held in various venues, of which the most imposing is the one finalized by Louis XV: the Royal Opera added to the north wing of the palace. The names of the great classics of the theatre can be linked to these spectacle events, such as Corneille, Racine, Molière, and also the musician Lully, the choreographer Beauchamp, or the intendant Viga- rani, not to mention the architectural spectacle resulting from the collaboration of the Sun King with his famous court artists: architects (Le Vau, Le Nôtre, Mansart, etc.) and painters (Le Brun, Poussin, etc.).